Acceptability, Willingness to use and Preferred Distribution Models of Oral- Based HIV Self-Testing Kits among Key and Priority Populations Enrolled in HIV Pre-Exposure Prophylaxis Clinics in Central Uganda. A Mixed-Methods Cross-Sectional Study - Matovu, John Bosco Junior; Mayega, Roy William; Nalubega, Sylvia; Byakika-Tusiime, Jayne (Archives of Clinical and Biomedical Research, 2022)
Background: Key Populations (KPs) and Priority Populations (PPs) taking Pre-Exposure Prophylaxis (PrEP) for HIV prevention require routine HIV testing every after three months hence can benefit from HIV self-testing (HIVST). We assessed the acceptability of oral-based HIVST among Key and priority Populations taking PrEP in central Uganda. Materials and Methods: A mixed methods cross-sectional study was conducted on 367 KPs and PPs attending PrEP clinics in central Uganda in August 2018. Quantitative data analysis included inferential statistics to determine associations between social-demographic and economic characteristics, and study outcomes using multivariable logistic regression, quoting p-values less than 5% at 95% confidence interval. Thematic analysis was performed to explore factors that promote and inhibit HIVST. Results: HIV self-testing acceptability; defined as the proportion of respondents who performed the test among those approached was 99.5% (365/367). Choice of HIVST was predicted by education level, (primary versus other: AOR 0.403; 95% CI 0.204-0.794; p<.009), willingness to pay for HIVST kits was predicted by clinic location (Urban vs Rural: AOR 0.041; 95% CI 0.018-0.97; p<.001) and KP category (FSW versus others: AOR 4.605; 95% CI, 1.497-14.172. Respondents who attained post-primary education preferred to pay less than 1.4 USD for an oral HIVST kit (AOR 2.064; 95% CI 1.006-4.237; p<.048). Oral fluid-based kit “Oraquick” was preferred over other HIV testing modalities because it was painless, convenient, easy to use and time saving. Conclusion: Oral-based HIV self-testing is highly acceptable among key and priority populations taking Pre-Exposure Prophylaxis and can be adopted as an alternative to the conventional routi